ANALISIS PERSEPSI MASYARAKAT TERHADAP ABK YANG BERSEKOLAH DI SEKOLAH UMUM - Adillah, adillah; Serawati, Serawati; Andriani, Opi; Prahagia, Yelvia (Program Studi Pendidikan Vokasi Seni Kuliner, 2023)
This article aims to analyze public perceptions of ABK who attend public schools. This research uses a qualitative descriptive research method. Data collection techniques include: observation, interviews included in the questionnaire data, and documentation. The research subjects or informants are the surrounding community. The results of the research show that the public's perception of children with special needs (ABK) who attend public schools is that parents' (community) attention to children with special needs is 60%, parents' (community) understanding of children with special needs is 87% and the importance of service quality according to parents (community) towards children with special needs is 93%. In accordance with Law Number 20 of 2003, CHAPTER IV article (5) paragraph (1), that every citizen has the same right to obtain quality education.